Study protocol: Developing telephone follow-up scale for patients with disorders of consciousness - Shou, Fangfang; Wang, Jing; Laureys, Steven; Cheng, Lijuan; Huang, Wangshan; Di, Haibo (Frontiers in Public Health, 2023)
Background: The significant lack of rehabilitation prognostic data is the main reason that affects the treatment decision-making and ethical issues of patients with disorders of consciousness (DoC). Currently, the clinic's consciousness assessment tools cannot satisfy DoC patients' follow-up needs. Objective: The purpose of this study is to construct a sensitive, professional, and simple telephone follow-up scale for DoC patients to follow up on the prognosis, especially the recovery of consciousness, of prolonged DoC patients transferred to community hospitals or at home. Methods: This study is to adopt expert consultation to construct and to verify the validity and feasibility of the scale on-site. Conclusion: At present, there is a strong demand for portable, accurate, and easily operated scales. It is helpful to improve the rehabilitation data of prolonged DoC patients and provide more basis for their treatment and rehabilitation.